Clinical features, diagnosis methods and evolution in non meningeal cryptococcosis in VIH positive patients. (Actualizaciones en Sida e Infectología, 2022)
Cryptococcosis is a serious mycosis that manifests itself, in 90% of cases, as meningoencephalitis, especially in AIDS patients. The objective of this study is to describe the extra-meningeal cases of cryptococcosis in people living with HIV and to know how many of them suffer from concomitant meningeal involvement. Also, to determine its relationship with the Cryptococcus capsular polysaccharide antigen titer in serum.A retrospective, observational and analytical study was carried out. HIV-positive patients whose initial diagnosis had been made from extrameningeal samples in the period between 2012 and 2019 were included. The patients were divided into 2 groups. Group 1: patients without meningeal involvement; group 2: those who finally had CNS involvement.Of a total of 531 cryptococcosis registered in this period, 113 patients (21%) were included, of whom meningeal involvement was confirmed in 58. No significant differences were observed in terms of mortality in both groups.None of the patients with positive LFA antigenemia (Capsular antigen detection by lateral Flow assay) but negative latex particle agglutination (LA) antigenemia had meningeal involvement. LFA was found to be highly sensitive and allows early diagnosis, but it does not replace other diagnostic procedures.Serum Cryptococcus antigen titers for by LA greater than or equal to 1/100 were found to correlate with a 30-fold increase in the likelihood of meningitis.In all cases, CNS involvement must be ruled out. LA continues to be a useful and complementary test, because in cases with negative LA, no meningeal involvement was observed.
Keywords: cryptococcal antigemia; extrameningeal cryptococcosis; cryptococcemia; pulmonary cryptococcosi; Cryptococcus